What drives the 'August effect'?: an observational study of the effect of junior doctor changeover on out of hours work - Blakey, John; Fearn, Andrew; Shaw, Dominick E. (SAGE, 2013)
Objective: To investigate whether measurements of junior doctor on-call workload and performance can clarify the mechanisms underlying the increase in morbidity and mortality seen after junior doctor changeover: the ‘August effect’.